WOMEN AND BIOTECHNOLOGY - Prakash, Seema; Sivaram, Latha (Ushus Journal of Business Management, 2003)
Women have always had a strong affinity to Biological Sciences, probably due to their intrinsic creative qualities. More recently, Biotechnology, a very knowledge-intensive discipline has become the forte of women. With the numerous benefits it has to offer to mankind and environment, Biotechnology has become a priority area in the country's Science and Technology agenda. Unlike as in the past, the near future will see active participation of women in policy and decision-making in the areas of research and education at both, national and international levels.